2023
DOI: 10.1007/s10548-023-01022-2
|View full text |Cite
|
Sign up to set email alerts
|

Longstanding Auditory Sensory and Semantic Differences in Preterm Born Children

Chrysa Retsa,
Hélène Turpin,
Eveline Geiser
et al.

Abstract: More than 10% of births are preterm, and the long-term consequences on sensory and semantic processing of non-linguistic information remain poorly understood. 17 very preterm-born children (born at < 33 weeks gestational age) and 15 full-term controls were tested at 10 years old with an auditory object recognition task, while 64-channel auditory evoked potentials (AEPs) were recorded. Sounds consisted of living (animal and human vocalizations) and manmade objects (e.g. household objects, instruments, and to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…In the study by (Retsa et al 2023), the long-term consequences of pre-term birth on auditory processing were investigated. The researchers recorded auditory eventrelated potentials (ERP) to environmental sounds (living vs. manufactured objects) in 10-year-old children born at term or very preterm.…”
Section: State and Trait Relations Of Microstatesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by (Retsa et al 2023), the long-term consequences of pre-term birth on auditory processing were investigated. The researchers recorded auditory eventrelated potentials (ERP) to environmental sounds (living vs. manufactured objects) in 10-year-old children born at term or very preterm.…”
Section: State and Trait Relations Of Microstatesmentioning
confidence: 99%
“…Additionally, parameters like the onset and offset of each microstate after stimulus onset become relevant temporal parameters (Michel et al 1999). Using this approach, (Retsa et al 2023) revealed significant differences between the two volunteers before they engaged in a virtual surfing task. Analyzing microstate features and correlating them with motor behavioral metrics, they observed that the pre-activation of microstate C, associated with the posterior default mode network (DMN), correlated with poorer performance in the subsequent motor task.…”
Section: State and Trait Relations Of Microstatesmentioning
confidence: 99%
“…The technique provides (sub) millisecond temporal resolution, allowing for precise characterization of both the amplitude and the topography of cortical activity over time during a visual task 17,18 . These robust EEG analyses have produced invaluable knowledge in sensory processing 1922 and pathologies 2327…”
Section: Introductionmentioning
confidence: 99%
“…The technique provides (sub) millisecond temporal resolution, allowing for precise characterization of both the amplitude and the topography of cortical activity over time during a visual task 17,18 . These robust EEG analyses have produced invaluable knowledge in sensory processing [19][20][21][22] and pathologies [23][24][25][26][27] Additionally, myopia and its defocus alter visual experiences during years when children are still fine-tuning their visual system. Illusory contour (IC) sensitivity, for one, matures through adolescence 28,29 .…”
Section: Text Introductionmentioning
confidence: 99%